Use of Project Based Learning Model to Improve Interpersonal Communication Skills of Class VIII Students in Science Subjects in MTs Raudhatul Ikhwan - Setiawan, Agus; Suhendar, Suhendar; Ramdhan, Billyardi (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2022)
Background: The lack of interpersonal communication skills of students will affect the learning process (teachers and students) looking for ways to take advantage of other learning models so that the learning process continues to run interestingly and remain meaningful. This study aims to develop a project-based learning model on human digestive system material in class VIII students at MTs Raudhatul Ikhwan. Methods: The development of this Project based learning model follows nurohman's development model. The stages of the model are the identification of potentials and problems, data collection, product design, design validation, design revision, product trial, product revision, usage trial, product revision. Results: Data from this study were obtained from validation by two experts, which were then tested on 38 class VIII learners and teachers at MTs Raudhatul Ikhwan. In cycle 1, the final data was obtained by around 71% and the second cycle increased to 78% so that the project-based learning so that the project based learning learning model deserves to be used as a learning medium with good categories. Keywords : Project based Learning, interpersonal communication, meaningful Retracted reason: method and citing problems